Pengaruh Brand Experience, Brand Trust Dan Brand Image Terhadap Brand Loyalty (Pada Pengguna Celana Jeans Merek Levi’s di Kota Padang) - Erita Erita; Syailendra Eka Saputra; Lara Maisyarani (Journal of Innovative and Creativity, 2024)
This study aimed to analyze the influence of brand experience, brand trust and brand image on brand loyalty (in the Levi's brand jeans in town field). The results of data analysis showed that: (1) There is significant influence between Brand Experience against Brand image on the Levi's brand jeans in Padang with values obtained coefficient of 0.306 with a p-value of 0.047 and thitung 1.992> 1.66 with ttabel with significant value p-value 0.047 <alpha of 0.05 (2) There is significant influence between brand Experience against brand Loyalty in the Levi's brand jeans in Padang with values obtained coefficient of 0.456 with a p- value of 0.007 and 2.700 thitung> ttabel of 1.66 with significant value p-value 0.007 <alpha of 0.05 (3) There is no significant influence among Against brand loyalty brand image on the Levi's brand jeans in Padang with coefficient of 0.220 with a p-value of 0.107 and thitung 1,614 <ttabel of 1.66 with significant value p-value 0.107> 0.05 alpha (4) There is a signifi influence Against right between the Brand Trust on the Brand image of Levi's jeans brand in Padang with coefficient of 0.552 with a p-value of 0.000 and thitung 3,544> t table value of 1.66 with a significant p-value of 0.000 <alpha 0.05 ( 5) There is no significant effect of brand trust on the brand Loyalty Against jeans brand Levi's in Padang with coefficient of 0.099 with a p-value of 0.529 and thitung 0,629 <ttabel of 1.66 with significant value p-value 0.529> alpha of 0.05.